Interface pressure, perceptual, and mean arterial pressure responses to different blood flow restriction systems. (30th April 2018) - Hughes, L.; Rosenblatt, B.; Gissane, C.; Paton, B.; Patterson, S. D.
Abstract : This study examined the cuff to limb interface pressure during blood flow restriction (BFR), and the perceptual and mean arterial pressure responses, in different BFR systems. Eighteen participants attended three experimental sessions in a randomised, crossover, counterbalanced design. Participants underwent inflations at 40% and 80% limb occlusive pressure (LOP) at rest and completed 4 sets of unilateral leg press exercise at 30% of one repetition maximum with BFR at 80% LOP. Different BFR systems were used each session: an automatic rapid‐inflation (RI), automatic personalized tourniquet (PT) and manual handheld pump and sphygmomanometer (HS) system. Interface pressure was measured using a universal interface device with pressure sensors. Perceived exertion and pain were measured after each set, mean arterial pressure (MAP) was measured pre‐, 1‐minute post‐ and 5‐minutes post‐exercise. Interface pressure was lower than the set pressure in all BFR systems at rest ( P < .05). Interface pressure was, on average, 10 ± 8 and 48 ± 36 mm Hg higher than the set pressure in the RI and HS system ( P < .01), with no differences observed in the PT system ( P > .05), during exercise. Pain and exertion were greater in sets 3 and 4 in the RI and HS system compared to the PT system ( P < .05). MAP was higher in the RI and HS system compared to the PT system at 1‐minute and 5‐minutes post‐exercise ( P < .05). BFR systems applying higher pressures amplify mean arterial pressure and perceptual responses. Automatic BFR systems appear to regulate pressure effectively within an acceptable range during BFR exercise.